Whole brain radiation therapy alone versus radiosurgery for patients with 1–10 brain metastases from small cell lung cancer (ENCEPHALON Trial): study protocol for a randomized controlled trial - Bernhardt, Denise (Trials, 2018)
BACKGROUND: Conventional whole brain radiotherapy (WBRT) has been established as the treatment standard in patients with cerebral metastases from small-cell lung cancer (SCLC), however, it has only modest efficacy and limited prospective data is available for WBRT as well as local treatments such as stereotactic radiosurgery (SRS). METHODS/DESIGN: The present single-center prospective randomized study, conducted at Heidelberg University Hospital, compares neurocognitive function, as objectively measured by significant deterioration in Hopkins Verbal Learning Test – Revised total recall at 3 months. Fifty-six patients will be randomized to receive either SRS of all brain metastases (up to ten lesions) or WBRT. Secondary endpoints include intracranial progression (local tumor progression and number of new cerebral metastases), extracranial progression, overall survival, death due to brain metastases, local (neurological) progression-free survival, progression-free survival, changes in other cognitive performance measures, quality of life and toxicity. DISCUSSION: Recent evidence suggests that SRS might be a promising treatment option for SCLC patients with brain metastases. The present trial is the first to prospectively investigate the treatment response, toxicity and neurocognition of WBRT and SRS in SCLC patients. TRIAL REGISTRATION: Clinicaltrials.gov NCT03297788. Registered September 29, 2017. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13063-018-2745-x) contains supplementary material, which is available to authorized users.